New Technology of Thermoplastic Coating for Osmotic Pump Tablets: Study on in vitro Drug Release - Chunping Yuan; Huimin Hou; Shuyun Ou; Shujing Zhao; Yongjian Gao; Qing Liu (Georg Thieme Verlag KG, 2019)
Abstract Aim The in vitro drug release profiles of metformin hydrochloride thermoplastic coated tablets and nifedipine thermoplastic coated tablets were studied. Methods By measuring the in vitro release profiles of the thermoplastic coated tablets of model drugs, the effects of membrane thickness, polyethylene glycol-1,500 (PEG1500) content, number of orifice, stirring speed, and release medium on the drug release were investigated, and the rule and mechanism of drug release were also analyzed by comparing with the osmotic pump tablets (OPTs). Results Thermoplastic coated tablets with single- or double-chamber construction performed the same function of controlling the drug release, operated under the same release mechanism (osmotic pressure drove the drug release), and exhibited the same release characteristics (zero-order release, unaffected by release medium, and stirring speed) and release rule (release rate was inversely proportional to the membrane thickness but proportional to the PEG1500 content) as compared with OPTs prepared by the common spray coating technology. Conclusion Thermoplastic coated tablets have the same release characteristics in vitro as OPTs. The new technology of thermoplastic coating can replace the spray coating technology of OPTs. This study provides theoretical basis and practical support for the industrialization and clinical application of thermoplastic coating technology.